L’Opéra en version anglaise : un enjeu esthétique ou sociologique ? - Pierre Degott (Revue LISA)
The history of English opera has always been conditioned by the ambivalent attitude of English-speaking audiences towards their own language. A close scrutiny of the London theatre seasons of the XVIIIth and XIXth centuries does indeed show a strong split, in terms of aesthetic and sociological considerations, between, on the one hand, the aristocratic Italian seasons of the King’s Theatre in Covent Garden, and the English opera seasons organised by the "lesser" theatres on the other. The aim of this paper is to assess the sociological implications of the use of the English language on the operatic stage. Far from defending the – now absurd – idea of the superiority of English over original versions, this paper shows that English versions of the main repertory were sometimes far ahead of their Italian counterparts at least in terms of artistry and musical authenticity. An example of such a phenomenon is provided by the Old Vic in the 1920s, when Edward Dent’s spirited translations of Mozart’s operas won the theatre the name of "the Home of Mozart." A comparative study of several translations of Mozart’s Le Nozze di Figaro further displays the interrelatedness of the sociological and aesthetic issues of operatic translation.